(untitled) (UNED Research Journal, 2025)
Introduction: The “Pacto de Concordia” is often regarded as Costa Rica’s first political constitution, making its preservation essential for safeguarding a document of such historical relevance. Objective: To evaluate its state of deterioration using validated scales and physicochemical techniques. Methods: Between March 2021 and December 2023, we applied an expert-validated deterioration scale and used multispectral photography to detect signs of damage, including acid hydrolysis, fungal activity, and other agents. Results: Most folios are in good condition, with deterioration indices ranging from 0% to 20%. Paper pH values ranged from 6,0 to 8,5, suggesting a risk of acid hydrolysis that could compromise the document over time. Conclusion: We recommend maintaining current conservation practices and periodically monitoring the folios’ pH to prevent further deterioration.